eCM 2011
DOI: 10.22203/ecm.v022a06
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and osteogenic differentiation of human periodontal ligament cells on akermanite and β-TCP bioceramics

Abstract: The purpose of this study was to investigate the effects of akermanite as compared to β-TCP on attachment, proliferation, and osteogenic differentiation of human periodontal ligament cells (hPDLCs). Scanning electron microscopy (SEM) and actin filament labeling were used to reveal attachment and growth of hPDLCs seeded on β-TCP and akermanite ceramic. Cell proliferation was tested by lactic acid production and MTT analysis, while osteogenic differentiation was assayed by alkaline phosphatase (ALP) expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 59 publications
2
71
0
Order By: Relevance
“…For cell morphology, 30 cells were seeded on the substrates in a 24-well plate at a density of 5.0×10 4 cells per mL. The nonadhered cells were removed by washing three times with phosphate-buffered saline after 24 hours of culture.…”
Section: Cell Morphology and Proliferationmentioning
confidence: 99%
“…For cell morphology, 30 cells were seeded on the substrates in a 24-well plate at a density of 5.0×10 4 cells per mL. The nonadhered cells were removed by washing three times with phosphate-buffered saline after 24 hours of culture.…”
Section: Cell Morphology and Proliferationmentioning
confidence: 99%
“…Interestingly, both N2 and N5 composites showed an early onset of Ca release (Figures 3 and 4). The release of Ca 2+ ions from HA 38 and other Ca-containing materials, such as beta-tricalcium phosphate 38,39 or akermanite, 39,40 has been shown to increase osteogenic cell differentiation, including the expression and synthesis of osteopontin. The addition of Ca 2+ ions directly to the culture media also stimulated the production of osteopontin.…”
mentioning
confidence: 99%
“…Recently, many investigators have demonstrated that implanted -TCP is resorbed by macrophagelike cells without cytotoxicity or inflammatory response [33,34]. -TCP degradation promotes concentration of calcium ions released into the regenerative space and alkaline phosphatase activity of osteoblastic cells [35,36]; these phenomena allow environmental changes for osteogenesis to occur. Histological specimens treated with the Journal of Nanomaterials nano-TCP scaffold at 10 days revealed foreign-body giant cells around the relatively large particles of -TCP in the scaffold.…”
Section: Discussionmentioning
confidence: 99%